Aktivitas Protease dan Kadar Protein Tubuh Ikan Lele Dumbo (Clarias gariepinus) pada Kondisi Puasa dan Pemberian Pakan Kembali - Wieka Mahalida Hanum; Untung Susilo; Slamet Priyanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
Three treatments and four replications in randomised completely design were conducted to reveal the protease activity and body protein content on catfish, Clarias gareipinus, under starvation and refeeding conditions. The result showed that the protease activity has no significant different (P>.05) in first week, but has significant different (P<.05) in second week after treatment. Body protein content has significant different (P<.05) in first and second weeks after treatment. We concluded that the protease activity and body protein content decreased at deprivation, but increased after two weeks refeeding.